Unidirectional gene pairs in archaea and bacteria require overlaps or very short intergenic distances for translational coupling via termination-reinitiation and often encode subunits of heteromeric complexes - Huber, Madeleine; Vogel, Nico; Borst, Andreas; Pfeiffer, Friedhelm; Karamycheva, Svetlana; Wolf, Yuri I.; Koonin, Eugene V.; Soppa, Jörg (Frontiers in Microbiology, 2023)
Genomes of bacteria and archaea contain a much larger fraction of unidirectional (serial) gene pairs than convergent or divergent gene pairs. Many of the unidirectional gene pairs have short overlaps of -4 nt and -1 nt. As shown previously, translation of the genes in overlapping unidirectional gene pairs is tightly coupled. Two alternative models for the fate of the post-termination ribosome predict either that overlaps or very short intergenic distances are essential for translational coupling or that the undissociated post-termination ribosome can scan through long intergenic regions, up to hundreds of nucleotides.We aimed to experimentally resolve the contradiction between the two models by analyzing three native gene pairs from the model archaeon Haloferax volcanii and three native pairs from Escherichia coli. A two reporter gene system was used to quantify the reinitiation frequency, and several stop codons in the upstream gene were introduced to increase the intergenic distances. For all six gene pairs from two species, an extremely strong dependence of the reinitiation efficiency on the intergenic distance was unequivocally demonstrated, such that even short intergenic distances of about 20 nt almost completely abolished translational coupling. Bioinformatic analysis of the intergenic distances in all unidirectional gene pairs in the genomes of H. volcanii and E. coli and in 1,695 prokaryotic species representative of 49 phyla showed that intergenic distances of -4 nt or -1 nt (= short gene overlaps of 4 nt or 1 nt) were by far most common in all these groups of archaea and bacteria. A small set of genes in E. coli, but not in H. volcanii, had intergenic distances of around +10 nt. Our experimental and bioinformatic analyses clearly show that translational coupling requires short gene overlaps, whereas scanning of intergenic regions by the posttermination ribosome occurs rarely, if at all. Short overlaps are enriched among genes that encode subunits of heteromeric complexes, and co-translational complex formation requiring precise subunit stoichiometry likely confers an evolutionary advantage that drove the formation and conservation of overlapping gene pairs during evolution.